Original paperIntracellular expression of Bcl-2 protein in lymphocytes T from children suffering from bronchial asthma - Ciepiela, Olga; Zawadzka-Krajewska, Anna; Kotuła, Iwona; Pyrżak, Beata; Lewandowska, Katarzyna; Demkow, Urszula (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : Bronchial asthma is a chronic inflammatory disease of airways, characterized by persistent T cells activation in peripheral blood and airways. A disrupted immunological balance between T helper lymphocytes could be a result of an improper apoptosis process within lymphocytes. An intracellular Bcl-2 dependent pathway is one of the pathways of programmed cell death. Aim : The aim of the paper was to evaluate the Bcl-2 expression in T lymphocytes from children suffering from bronchial asthma. Material and methods : Peripheral blood from 25 asthmatic children, aged 8.13 ±3.08 with positive results of skin prick tests or in vitro tests detecting specific IgE against allergens of pollen grass, and 16 healthy children, aged 9.38 ±3.52 was analyzed. The Bcl-2 expression in T CD2+, Th1 CCR5+ and Th2 CRTh2+ lymphocytes was measured with flow cytometry. Results . The percentage of T lymphocytes from peripheral blood of asthmatics and healthy controls was 72.8 ±8.79% and 79.07 ±6.21%, respectively, p < 0.05. No difference was found between the frequency of Th1 cells from asthmatic and healthy subjects, however a significant difference in the Bcl-2 expression was observed between both groups (53.82 ±30.00% vs. 75.86 ±20.11%, p < 0.05). The significant difference was found between the frequency of Th2 cells from asthmatic (6.51 ±4.46%) and nonasthmatic (3.01 ±1.26%) individuals, nevertheless cells did not differ in the Bcl-2 expression. Conclusions : The imbalance between Th1 and Th2 cell subpopulations is found in asthma. An increased frequency of Th2 cells may result from a decreased Bcl-2 expression within Th1 lymphocytes and increased susceptibility to apoptosis.